A New Challenge: The Reconstruction of Online Language Laboratory on Distance Learning - Tatas Transinata (Educational Challenges, 2022)
The Covid-19 wide spread constrained numerous schools and colleges to stay closed briefly. This phenomenon brings a challeging in teaching learning process. The aim of this paper is to explain the learning process using new language laboratory format. There can be several formats of online learning process: Knowledge base, online support, asynchronous training, synchronous training, and hybrid training. This study employed a descriptive design with a qualitative approach to examine the language laboratory strategis and challenges through the pandemic in the University. A questionnaire and interview were used in this study to elicit the responses of English Lecturer in Language Center, Sebelas Maret University. The findings reveal that the coronavirus disease 2019 (COVID-19) pandemic has reformed the Language Laboratory significantly. Both lecturers and students in are faced with multiple challenges in conducting teaching and learning process. In other hand, the new format and content of Online language laboratory helps teachers and students in teaching learning process. Covid-9 also opens an opportunity to reconstruct the teaching learning system in laboratory and establish updated programs and assessments.